Delavsko gibanje v Trstu 1920-1921 - Gombač, Boris (Inštitut za novejšo zgodovino, 1981)
The author discusses certain aspects of the Trieste working classes and the reaction of their political organizations and trade unions to the new structures of the Italian capital which after the year 1918 replaced the Austro-Hungarian on the Trieste capital market. The social and national problems of the Trieste socialists coincided with marked fractional conflicts within the Italian Socialist Party. The intervention of fascism and the repressive power of the State suppressed the revolutionary zeal of the Trieste working classes. Avtor obravnava nekatere aspekte delavskega razreda v Trstu, ter reakcijo njegovih političnih in sindikalnih organizacij na nove strukture italijanskega kapitala, ki je po letu 1918 na tržaškem tržišču zamenjal avstroogrski kapital. Socialni in nacionalni problemi tržaških socialistov se križajo s poudarjenimi frakcijskimi boji v sami italijanski socialistični stranki. Poseg fašizma in državne represivne sile izničijo revolucionarni polet tržaškega delavstva.